ANALYSIS OF SCHOOL COOPERATIVE MANAGEMENT BY MANAGEMENT AT MAN 1 TEGAL - Dwi Prasetyono , Septian (Mount Hope Economic Global Journal, 2023)
This research aims to determine implementation planning and student responses to the management of school cooperatives at MAN 1 Tegal. The research method used is a descriptive method with the form of research used is a survey. The results of data analysis show that the management of the school cooperative is very good. Based on the results of distributing questionnaires to cooperative members, namely class X and XI students. In accordance with the plan that has been agreed with a total of 82.87%, this is in accordance with the students' wishes regarding cooperative management. Apart from that, the implementation of cooperative management is very good due to the awareness of all cooperative administrators. This makes it easier for each member to provide services provided by the cooperative management